Pengaruh Kompensasi, Pelatihan, Dan Peran Supervisor Terhadap Kinerja Yang Dimediasi Oleh Kepuasan Kerja Pada Karyawan Paguyuban Batik Laweyan Surakarta - Mutmainah, Hestin (Graduasi: Jurnal Bisnis & Ekonomi, 2013)
This research has the aim to testing corelation among variables to reality faced are the poor performance of employees Batik Club at Laweyan, Surakarta. The population is all of ceaftman of batik club at Laweyan Surakarta. The samples amount take with forecasting interval, and use the purposive sampling method to take the samples. The result of this research show thah compensation and training variables have not significance (P > 0,05) influence to job satisfaction and also have no significance influence to employee performance. But the supervisor role variable has the significance (P < 0,05) influence both to the job satisfaction and also to employee performanceÂ  Batik Club at Laweyan, Surakarta. Â And than, based on the result of mediating test show that job satisfaction variable in reality mediates the correlation between compensation, training, and supervisor reole with the employee performance.